2015
DOI: 10.1016/j.surg.2014.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Extending the value of the National Surgical Quality Improvement Program claims dataset to study long-term outcomes: Rate of repeat ventral hernia repair

Abstract: Long-term rate and timing of ventral hernia re-repair obtained from claims data were an underestimate compared with clinical studies. Yet, several known clinical risk factors for recurrence in the clinical registry were associated with the re-repair rate in claims data at one year. It may be possible to study certain long-term outcomes using selected reoperation rates using the technique of linked clinical registry-claims data, with an understanding that event rates are conservative estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…An analysis of any incisional or ventral hernia repairs in the American College of Surgeons National Surgical Quality Improvement Program identified risk factors for recurrence within 1 year (age, postoperative superficial surgical site infection, steroid use, smoking, increasing American Society of Anesthesiology score, and BMI). 14 Similar to our study, increasing age was associated with decreasing risk for recurrence and being a smoker increased recurrence risk. In comparison, a Danish study identified defect size, prior hernia repair, and nontacking fixation (for laparoscopic surgery) as risk factors for hernia repair reoperation.…”
Section: Discussionsupporting
confidence: 88%
“…An analysis of any incisional or ventral hernia repairs in the American College of Surgeons National Surgical Quality Improvement Program identified risk factors for recurrence within 1 year (age, postoperative superficial surgical site infection, steroid use, smoking, increasing American Society of Anesthesiology score, and BMI). 14 Similar to our study, increasing age was associated with decreasing risk for recurrence and being a smoker increased recurrence risk. In comparison, a Danish study identified defect size, prior hernia repair, and nontacking fixation (for laparoscopic surgery) as risk factors for hernia repair reoperation.…”
Section: Discussionsupporting
confidence: 88%
“…3,6,14,15 All panel participants agreed that they would not perform elective surgery on an active smoker. 3,6,14,15 All panel participants agreed that they would not perform elective surgery on an active smoker.…”
Section: Explanation Of Panel Discussionmentioning
confidence: 99%
“…Commonly practiced techniques for hernia repair use mesh, which is placed either in a sublay or onlay position. 7 This study was conducted on a population of total 94 patients, predominantly male. The correction of ventral hernia is a complex challenge in surgical practice with the use of numerous types of mesh to close the defect and strengthen the musculofascial tissues to prevent return.…”
Section: Discussionmentioning
confidence: 99%